2017
DOI: 10.1002/mrd.22876
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin regulates ovarian steroidogenesis during delayed embryonic development in the fruit bat, Cynopterus sphinx

Abstract: Cynopterus sphinx, a fruit bat, undergoes delayed embryonic development during the winter months, a period that corresponds to low levels of progesterone and estradiol synthesis by the ovary. Kisspeptins (KPs) are a group of neuropeptide hormones that act via G-protein coupled receptor 54 (GPR54) to stimulate hypothalamic secretion of Gonadotropin-releasing hormone, thereby regulating ovarian steroidogenesis, folliculogenesis, and ovulation. GPR54 is also expressed in the ovary, suggesting a direct role for KP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The expression of kisspeptin and KISS1R in buffalo ovary is affected by the follicles, and the expression is higher in the GCs of the follicles with high P4 concentration [ 16 ], indicating the potential relationship between kisspeptin and P4 synthesis. Previous studies suggest that kisspeptin could stimulate P4 synthesis in porcine, chicken, rat, and bat ovarian GCs [ 17 , 18 , 19 , 20 ]. However, the effect and mechanism of kp-10 on P4 synthesis in bovine ovarian GCs (BGCs) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of kisspeptin and KISS1R in buffalo ovary is affected by the follicles, and the expression is higher in the GCs of the follicles with high P4 concentration [ 16 ], indicating the potential relationship between kisspeptin and P4 synthesis. Previous studies suggest that kisspeptin could stimulate P4 synthesis in porcine, chicken, rat, and bat ovarian GCs [ 17 , 18 , 19 , 20 ]. However, the effect and mechanism of kp-10 on P4 synthesis in bovine ovarian GCs (BGCs) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, levels of StAR, CYP11a and 3β-HSD transcripts were also increased by KP-10 in the rat luteal cells (Peng et al, 2013). Recently, Anuradha and Krishna (2017) have also reported increased expressions of StAR and 3β-HSD in response to KP-10 in bat ovarian explants. Thus, these few studies in mammalian species support our notion of KP-10-stimulated gonadal steroidogenesis.…”
Section: Gonadal Steroidogenesismentioning
confidence: 74%
“…However, non-availability of such studies makes us difficult to correlate and discuss the present findings. Nevertheless, few studies on mammalian species are available (Anuradha and Krishna, 2017;Peng et al, 2013;Xiao et al, 2011). Xiao et al (2011) have shown that mammalian kisspeptin-10 up-regulates the expressions of, P450scc and StAR in cultured chicken granulosa cells.…”
Section: Gonadal Steroidogenesismentioning
confidence: 99%
“…The production of higher levels of E 2 in the kisspeptin supplemented groups in our study goes parallel with Sirotkin (2014), in which they reported that the support provided by kisspeptin towards the developing follicles in proliferation and further growth was by stimulating granulosa cells to secrete Estradiol‐17β during culture. Nonsignificant increase in the concentration of E 2 during culture (Group I; Table 1) is in line with earlier observation in fruit bat luteal cells cultured in lower concentrations of kisspeptin (Anuradha and Krishna A., 2017). In contrast Peng et al (2013) reported the production of progesterone but not Estradiol‐17β in the cultured luteal cells indicating the possibility of E 2 secretion and its regulation was an indirect action of KP through hypothalamic neuronal networks controlling GnRH secretion (Castellano et al, 2010).…”
Section: Discussionmentioning
confidence: 95%